Influence of diffusion and impedence parameters on wave propagation in thermoelastic medium - Kaushal, Sachin; Kumar, Rajneesh; Parmar, Kulwinder (Zielona Góra: Uniwersytet Zielonogórski)
The aim of the present paper is to study the impact of diffusion and impedance parameters on the propagation of plane waves in a thermoelastic medium for Green and Lindsay theory (G-L) and the Coupled theory (C-T) of thermoelasticity.
Keywords: plane waves; amplitude ratios; diffusion; impedance parameters